Essays on financial instability and crises - Elard, I (2015)
The thesis presents three papers in macroeconomics and monetary economics with an emphasis on financial instability and crises. The first paper, entitled "Interbank Market Crises and Financial Openness," studies the effect of financial openness on financial stability by extending a closed-economy DSGE model (Boissay, Collard and Smets, 2015) to an open economy in which banks are allowed to invest abroad. Financial internationalisation in the form of outward banking flows alters the behaviour of the economy in the run up to a typical interbank crisis, reducing the role played by domestic credit build ups. Prior to an interbank crisis, the level of assets typically builds up in an economy without access to international investment opportunities. In contrast, financial openness attenuates the build up of assets during productivity booms, which reduces the likelihood of financial overheating resulting in a banking crisis once productivity reverts to trend. Simulations of the model show that the open economy would generally experience fewer banking crises in the long run compared to an economy blocked from investing abroad. This finding may not obtain in the short run, however, should the economy be subject to large negative productivity shocks consequent upon a financial opening up to the external domain. The second paper, entitled “Unconventional Monetary Policy and Asset Allocation of International Mutual Funds,” a joint work with Gino Cenedese and Menno Middeldorp (both at the Bank of England), analyses the spillovers of unconventional monetary policy from the US to the Rest of the World. Using panel regressions on a fund-level data-set of globally domiciled mutual funds, the study examines the degree to which the operations and surprises of US unconventional monetary policy prompt mutual fund managers to change their portfolio country weightings.Our study permits an analysis of the portfolio choice of mutual fund managers, as differentiated from the portfolio rebalancing behaviour of their underlying investors. It allows for a quantitative examination as to whether and to what extent fund managers undo or exacerbate the allocation decisions by their respective underlying investors. Unconventional monetary policy by the US Federal Reserve is found to induce fund managers to reduce their portfolio exposure to the US whilst increasing it to other countries in the Rest of the World. Specifically, the Fed's purchases of Treasury securities trigger portfolio rebalancing in equity funds, while its acquisition of mortgage backed securities and agency debt has a minimal effect on equity and bond fund portfolio allocations. Fed policy surprises do affect the portfolio allocations of equity funds. The main results continue to hold in a number of robustness checks. An extension of the study examines portfolio rebalancing effects of policy surprises by three other major monetary authorities, the ECB, BoJ and BoE. The main focus of the paper, however, is on the broader effects of US unconventional monetary policy on the asset allocation of international mutual funds. The third paper, entitled "Sovereign Debt Negotiations as a Macroeconomic Game with Strategic Interactions among Players," aims to show that existing methods analysing games with more than two players can be usefully applied to macroeconomic games involving strategic interactions among three or more players. This is shown in the context of sovereign refinancing negotiations which are modelled as a bargaining game between three players: a debtor country in need of finance (player 1); its creditors from the international official-sector (player 2); and its foreign private-sector creditors in the form of international banks (player 3). The presence of a third player has important effects on the distribution of the gains from trade and the stability of the game if one allows for the possibility that any two players may form a coalition against another player. After deriving these general results, the model is applied to the Greek sovereign debt crisis to provide an economic application and to show that the framework can be applied to a wide range of other macroeconomic games.